Measurable impact of acupuncture on mucosal swelling of inferior turbinates: a prospective, randomized, controlled study - Albrecht, Tobias; Wu, Sa; Baumann, Ingo; Plinkert, Peter K.; Sertel, Serkan (Acta oto-laryngologica, 2015)
Conclusions: Sham acupuncture turned out to be more effective than expected. The effect of acupuncture cannot be assessed by optical rhinometry (ORM). Objectives: In most cases nasal congestion is caused by hypertrophy of the inferior turbinate as a result of allergic and chronic rhinitis. Topical decongestants cause severe side effects. As a consequence, there is an increasing demand for alternative treatment options such as traditional Chinese medicine (TCM). Methods: A total of 25 patients with nasal congestion due to hypertrophic inferior turbinate were recruited. The mucosal swelling status of the inferior turbinate was assessed by continuous ORM for 20 min. Patients were asked to score the severity of their nasal congestion on a visual analogue scale (VAS) before and 10 and 20 min after acupuncture. Specific verum acupuncture points related to nasal congestion were tested against non-specific control sham acupuncture points. Results: Sham acupuncture improved VAS scores, whereas ORM measured an increase in nasal swelling. The ORM revealed a quicker onset of the effect of verum acupuncture on the nasal blood flow. Also, verum acupuncture reaches its maximum effect in a shorter time period, so that the net reaction time was much shorter. However, ORM could not prove a decongestant effect of verum acupuncture on inferior turbinate.